Religion und arkane Hierarchie : der Orden der Gold- und Rosenkreuzer als geheime Kirche im 18. Jahrhundert - Geffarth, Renko D. (Aries book series,, 2007)
This volume examines the history of the 18th-Century secret order of the Golden Rosicrucians (Gold- und Rosenkreuzer), one of the most mysterious, exclusive and successful Masonic societies in the German speaking countries of that time. The order and its esoteric roots have so far never been examined on the basis of original documents. The formation and development, the hierarchical structure, leading figures such as princes and ministers, and the system of degrees and secret teachings are explored in-depth and interpreted applying recent and innovative concepts of the Study of Western Esotericism.